Strategi Komunikasi Digital akun Instragram @cegah.narkoba terhadap Pencegahan Penyalahgunaan Narkoba - Hilmiaturrohmah Nur Habibah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Digital Communication strategies employed by the Instagram platform @cegah.narkoba, an initiative under the Prevention and Community Empowerment Division of the National Narcotics Agency of East Java Province (BNNP Jawa Timur), in promoting public awareness of drug abuse prevention. Using a sociological perspective, this study analyzes how visual narratives, symbolic interaction, and audience engagement contribute to the construction of collective meanings related to anti-drug norms in digital spaces. Through qualitative content analysis, the research explores visual content, messaging strategies, and interactive features utilized on the platform. The findings indicate that @cegah.narkoba consistently employs persuasive visuals, symbolic elements, and interactive communication to effectively reach young audiences and reinforce preventive values. Additionally, collaborations with community organizations, educational institutions, and local influencers enhance message dissemination and strengthen campaign credibility. Overall, the study highlights Instagram’s role as a strategic social medium that not only disseminates information but also facilitates the internalization of anti-drug values through shared symbols and participatory engagement.